A Pathway to Immersive Storytelling: From Linear to Participatory: Reflecting on the Artistic XR works of Michelle & Uri Kranot - Kranot, Michelle; Kranot, Uriel (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
This paper contributes to understanding XR, animation, and participatory storytelling intersections by documenting and reflecting on creative processes. This account illustrates the Kranots’ trajectory through six stages of practice and research, illustrated by personal artistic works. The authors argue that the integration of performance, animation, and XR enriches creative industries and educational contexts, adding meaning and practical value. Their process begins with ‘performative immersion’, followed by ‘passive witnessing’ and ‘immersion through interaction’. The process is further explored in ‘immersion through being’ and ‘immersion through shared experience’. Their current stage of investigation concludes the process with the examination of ‘real-time narratives’. This research traces a personal artistic journey from linear to participatory storytelling, while providing a structured pathway for other artists and researchers to explore similar practices.